6-7 gadīgu bērnu pamatkustību apguves sekmēšana kustību rotaļās - Siļina, Ira (Latvijas Universitāte, 2018)
Pētījuma tēma: 6-7 gadīgu bērnu pamatkustību apguves sekmēšana kustību rotaļās. Pētījuma mērķis: pētīt pamatkustību sekmēšanas iespējas 6 – 7 gadīgiem bērnu kustību rotaļās. Informācijas iegūšanai par pētāmo problēmu, analizēta pedagoģiski psiholoģiski zinātniskā literatūra. Izmantotas pedagogu un psihologu R. Jansones, D. Dzinteres, I. Stangaines, I. Granta, R.Karlovskas, V. Krauksta, L. Kurzemnieces, A. Kuznecova, S. Laizānes, D. Lieģenieces, A.Ļubļinska, G. Svences u.c. atziņas. Teorētiskā daļā aplūkotas: pamatkustību attīstīšanas nozīmīgums pirmsskolā; pamatkustību raksturojums; 6-7 gadīgu pirmsskolas vecuma bērnu attīstības raksturojums; rotaļas būtībā un tās nozīme; kustību rotaļas pamatkustību attīstīšanas kontekstā. Praktiskajā daļā pētītas kustību rotaļu izmantošanas iespējas 6-7 gadus veciem bērniem pamatkustību attīstīšanai. Būs veikta pedagoģiskā novērošana, būs organizēta pedagoģiskā eksperimenta darbība un analizēti pētījuma rezultāti. Pētījuma gaitā tiks aprobēta izstrādāta kustību rotaļu kopa, analizēta kustību rotaļu ietekme uz pamatkustību attīstību 6 – 7 gadus veciem bērniem. Atslēgas vārdi: attīstība, pamatkustības, kustību rotaļas.

Research theme: Enhancing learning movement skills in motion games for 6 – 7 years olds. The aim of the research: to study rating possibilities of the basic movement of development of 6-7 years olds physical possibilities using the games of motions. Keywords: basic movements, motions games, development. The scientific pedagogical and psychological literature is analysed to get the information on the studied problem. Teachers and psychologists R.Jansone, D. Dzintere, 1. Stangaine, J.Grants, R. Karlovska, V. Krauksts, L. Kurzemniece, A.Kuzņeeova, S. Laizāne, D. Lieģenieee, A. Ļubļinska, G. Svence u.c. conclusions are used. In the theoretical part are examined: •the children's basic movements developing possibilities in a pritnary school; • description of the basic movements; •6 - 7 years olds developing characteristics;the essenee of the game and its meaning; •the game of motions in the context of the development of the basic movements. In the practical part of the work are observed the possibilities to use motion games to promote thc development of the 6-7 years olds basic rnovements . Pedagogical shadowing were done, also the action of pedagogical experiment was organized. The results of the researeh are analysed. Ouring the observation time the worked out games were approbated, analysed the influence of the motion games on the developrnent of 6 - 7 years olds basic movements. The research results testify that notieing the peculiarities of the infantile's age, as well as organizing the motion games systematieally and corretly, the development of the basic movements is promoted.
Enhancing learning movement skills in motion games for 6-7 year olds
Keywords: Pirmsskolas pedagoģija; attīstība; pamatkustības; kustību rotaļas; aktivitātes